2009
DOI: 10.1158/0008-5472.can-09-2226
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Antigen–Specific FOXP3+ CD4 T Cells Identified in Human Metastatic Melanoma: Peptide Vaccination Results in Selective Expansion of Th1-like Counterparts

Abstract: We have previously shown that vaccination of HLA-A2 metastatic melanoma patients with the analogue Melan-A 26-35(A27L) peptide emulsified in a mineral oil induces ex vivo detectable specific CD8 T cells. These are further enhanced when a TLR9 agonist is codelivered in the same vaccine formulation. Interestingly, the same peptide can be efficiently recognized by HLA-DQ6-restricted CD4 T cells. We used HLA-DQ6 multimers to assess the specific CD4 T-cell response in both healthy individuals and melanoma patients.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
(144 reference statements)
3
32
0
Order By: Relevance
“…They also did not generate a huge number of T cell lines when pools of peptides were used as immunogens, suggesting that either these T cells are not able to be expanded or that our culture conditions are not appropriate for their expansion. Spontaneous CD4 T cell responses to the cancer Ag OCT4 or MUC-1 have already been observed in healthy donors (43,44), but remained unusual as compared with other tumor Ags (8,11,12,45,46). For the first time, to our knowledge, we demonstrated that the spontaneous CD4 T cell response to CCNB1 persists in cancer patients and is not therefore dampened by the tumors.…”
Section: Discussionsupporting
confidence: 55%
“…They also did not generate a huge number of T cell lines when pools of peptides were used as immunogens, suggesting that either these T cells are not able to be expanded or that our culture conditions are not appropriate for their expansion. Spontaneous CD4 T cell responses to the cancer Ag OCT4 or MUC-1 have already been observed in healthy donors (43,44), but remained unusual as compared with other tumor Ags (8,11,12,45,46). For the first time, to our knowledge, we demonstrated that the spontaneous CD4 T cell response to CCNB1 persists in cancer patients and is not therefore dampened by the tumors.…”
Section: Discussionsupporting
confidence: 55%
“…After 7 days, antigen-specific Teffs and Tregs were examined by flow cytometry in inguinal dLNs and spleen. We initially vaccinated mice with OVA peptide alone, OVAþCpG AEIFA to determine whether this system could faithfully reproduce the effect observed in the blood of patients with melanoma vaccinated with MelanAþCpGþIFA (21). This was indeed the case, with CpG AEIFA significantly increasing the OVA-specific Teff:Treg ratio in vaccine-dLNs and spleen (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…In a clinical study of patients with melanoma immunized with NY-ESO-1 protein in ISCOMATRIX, vaccination increased the frequency of NY-ESO-1-specific Tregs in peripheral blood mononuclear cells (PBMC) and tumor tissue (20). We have shown that therapeutic vaccination of patients with melanoma with Melan-A peptide plus CpG-ODN in Montanide results in robust expansion of Melan-A-specific CD8 þ T cells within PBMCs with a concomitant decrease in Melan-A-specific Tregs (1,2,21). Importantly, although we observed a decrease in vaccine-specific Tregs, the total polyclonal Treg population remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to CD8 C T cells, CD4 C T cells recognize epitopes presented by MHC class II molecules and libraries of longer (20-mer) overlapping peptides are generally used to screen for antigen-specific responses. 19 We thus measured the response of Melan-A/ MART-1 [25][26][27][28][29][30][31][32][33][34][35][36] -specific CD4 C T-cell clones 20 spiked into PBMCs of HLA-DQ6 C donors in the presence of 20-mers overlapping peptide pools (1 mM each). As shown in Fig.…”
Section: Apc-mediated Stimulationmentioning
confidence: 99%